Empower Wall: Active insulation system leveraging additive manufacturing and model predictive control. (15th August 2022) - Atkins, Celeste; Hun, Diana; Im, Piljae; Post, Brian; Slattery, Bob; Iffa, Emishaw; Cui, Borui; Dong, Jin; Barnes, Abigail; Vaughan, Joshua; Roschli, Alex; Salonvaara, Mikael; et al.
Highlights: An innovative building envelope called Empower Wall was designed and tested. The smart wall integrates with both thermal energy storage and active insulation. Model predictive control was implemented to optimize energy consumption and cost. The prototype system demonstrated the ability for both energy and cost savings. Abstract: Buildings are one of the largest energy consumers worldwide, using large amounts of energy during their construction and for climate control during operation. Active insulation systems (AIS) have been shown to reduce the energy needed for climate control in buildings by dynamically regulating the heat transferred between a building's interior and exterior. Infrastructure-scale additive manufacturing (AM) has the potential to reduce the resources needed for building construction. Combining these two technologies into a single building envelope would create a path towards more sustainable buildings. A test was conducted for the Federal Energy Management Program (FEMP) Energy Exchange training and trade show, in August 2021, to investigate a new building envelope design, termed the Empower Wall, that utilized an AIS and was constructed using AM. Model predictive control was implemented to manage operation of the Empower Wall in concert with the existing HVAC system. The prototype system demonstrated that the Empower Wall lowered total energy consumption and reduced the cost of energy used.